PENGARUH WEBSITE QUALITY TERHADAP ONLINE BOOKING INTENTION DENGAN MEDIASI E-TRUST PADA PENGGUNA TRAVELOKA DI KOTA PADANG - Fajar Syah Putra; Rahmiati Rahmiati (Universitas Negeri Padang, 2019)
The purposes of this researches are to analyze: (1) The effect of Website quality and E-trust on Online Booking Intention of Traveloka users in the city of Padang, (2) The effect of Website Quality on E-trust of Traveloka users in the city of Padang. This type of research is causative research. The population in this study is the people of Padang who have accessed the Traveloka site. The sample used was 400 respondent using purposive sampling technique. Data was collected through questionnaires distributed online and analyzed using the SmartPLS version 3.0 program. The results of this study indicate that: (1) Website quality has a significant effect on Online Booking Intention with a coefficient value of 0.277 at P Values 0.005 and T statistics at 2.812, (2) Website quality has a significant effect on E-trust with a coefficient of 0.764 on P Values 0,000 and T statistics 18.444, (3) E-trust has a significant effect on Online Booking Intention with a coefficient value of 0.484 in P Values 0.000 and T statistics 5.981.Keywords : Website Quality, E-trust, Online Booking Intention